A CADEIA PRODUTIVA DO TABACO NA ECONOMIA BRASILEIRA: UMA ANÁLISE MULTISSETORIAL/ The tobacco production chain in the Brazilian economy: a multisectoral analysis - dos Santos Nunes, Wagner; Pinheiro Vieira, Leandro; da Rocha Gonçalves, Rodrigo; Rocha de Oliveira, Cassius (Informe GEPEC, 2024)
Este estudo investigou a interrupção parcial ou total do setor/atividade de fabricação de produtos de fumo, com o objetivo de quantificar a perda percentual na produção nacional em caso de uma interrupção hipotética deste setor, parte da cadeia produtiva do tabaco. Utilizando a abordagem da Matriz Insumo Produto (MIP) e o Método de Extração Hipotética (MEH), a fabricação de produtos de fumo foi artificialmente excluída, e o impacto dessa exclusão sobre o valor total da produção da economia brasileira foi avaliado. Foram utilizados os dados da Matriz de Insumo-produto Nacional de 2018, estimada pelo Núcleo de Economia Regional e Urbana (NEREUS/USP). Os resultados indicam que a eliminação hipotética da atividade de fabricação de produtos de fumo resultaria em uma contração de 0,15% do valor bruto da produção, 0,14% do valor adicionado e 0,18% no emprego no Brasil em todos os setores. Portanto, o estudo indica que a interrupção da fabricação de produtos de fumo gera perdas econômicas, afetando mais significativamente os setores de agricultura, comércio por atacado e transporte terrestre. Abstract: This paper investigated the partial or total interruption of the tobacco product manufacturing sector/activity, with the objective of quantifying the percentage loss in national production in the event of a hypothetical interruption of this sector, part of the tobacco production chain. Using the Input Output Matrix (IOM) approach and the Hypothetical Extraction Method (HEM), the manufacture of tobacco products was artificially excluded, and the impact of this exclusion on the total value of production in the Brazilian economy was assessed. Data from the 2018 National Input Output Matrix, estimated by the Regional and Urban Economy Center (NEREUS/USP), were used. The results indicate that the hypothetical elimination of the tobacco product manufacturing activity would result in a contraction of 0.15% in the gross value of production, 0.14% in value added and 0.18% in employment in Brazil in all sectors. Therefore, the study indicates that the interruption of the manufacture of tobacco products generates economic losses, most significantly affecting the agriculture, wholesale trade and land transport sectors.